Features of coping-behavior of medical workers during the COVID-19 pandemic - Pomytkina, Liubov Vitaliivna; Ichanska, Olena Mykhailivna (Insight: the psychological dimensions of society, 2021)
The article presents the results of a theoreticaland empirical study of coping-behavior of medical workersduring the COVID-19 pandemic, as in the threateningconditions of the pandemic, the professional activityof doctors is associated with extreme conditions thatrequire maximum tension on physiological and mentalfunctions. The purpose of the research was to find outthe main differences in the choice of coping-behaviorstrategies at the conscious and subconscious levelsof doctors during the pandemic, depending on the formof ownership of the medical institution. The researchmethodology was based on the general scientific principles of activity and personality approaches in psychology,as well as on the basic statements of the structuraltheory of ego-protection of R. Plutchic. Suchpsychodiagnostic methods were used: “Strategies forovercoming stressful situations” (SACS) of S. Hobfolladapted by N. Vodopyanova, E. Starchenkova; diagnosisof psychological protective mechanisms of the personalityof Plutchik-Kellerman-Conte “Life Style Index”(Life Style Index, LSI); WHO quality of life questionnaire(WHOQOL-100). As a result, there were significantdifferences in the coping-behavior of private clinicdoctors, who are less likely to demonstrate antisocialmodels of behavior (at the level of p≤.05), more oftenuse the mechanism of displacement than substitution(at the level of p≤.05), have much higher indicatorsof intellectualization mechanism (at the level of p≤.01),more prone to excessively mental way of overcomingfrustrating experiences; from all spheres of life significantdifferences (at the level of p≤.05), as well ashigher indicators (at the level of p≤.05) of quality of lifein the “spiritual sphere”, which indicates the presenceof strong personal beliefs that help to successfully copewith most difficulties in professional activity, givinganswers to spiritual and personality questions. Conclusions.The obtained data will allow to build a systemof psychological work to increase the level of constructiveand reduce the level of destructive coping-strategiesof doctors, the development of proactive copingas a system of personal resources that will help doctorsprepare to overcome the negative consequencesof future stressful situations.
Keywords: coping strategies, medical workers, mechanisms of psychological protection, pandemic, behavior, quality of life